INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM DALAM BUDAYA MUNA TEMBE NGGOLI PADA MASYARAKAT - Ardiansyah; Syarifan Nurjan; Muh. Tajab; Muhammad Abdul Rahim (LPPM STAI Muhammadiyah Probolinggo, 2023)
Culture is born and develops from the human mind which is passed down from generation to generation so that it becomes a custom that must be carried out. In daily life, this culture merges and follows the pattern of social life so that it gives various meanings. Integration, internalization and implementation of culture produce a work that is different in each region and has its own uniqueness and characteristics which indicate the character of the people even though they have the same function and role, but in its application, culture in each region has special characteristics that are unique and in accordance with the circumstances that society. As is the case with the muna tembe nggoli culture of the Ntobo people of Kota Bima. In this study, researchers want to try to examine the elements of values and the internalization of Islamic education values contained therein. This research has several objectives, namely 1) To describe and analyze the existence of Islamic education and its relationship with culture. 2) To describe and analyze the educational values in the process of making muna tembe nggoli. 3) To describe and analyze the internalization of the values of Islamic education in the culture of muna tembe nggoli which are applied in people's daily activities. The type of research used is field research using descriptive qualitative methods. The data is obtained by means of observation, interviews or interviews, field notes, and documentation. With this method researchers can see directly, interact and dig up information related to the object being studied. The research instruments were the researchers themselves and supporting instruments in the form of observations, interview guides, field notes, documentation and cell phones. The data analysis technique is triangulation. The stages of data analysis in research are by reducing, presenting, classifying, checking the validity of the data, verifying and drawing conclusions. As for the results of this study, the authors found several elements of Islamic values, namely ethical, aesthetic, moral and religious values contained therein. This value comes from the procedure for making and using tembe nggoli after it has been made. The internalization of these values is contained in the daily implementation of people who still adhere to ancestral culture based on Islamic law, although many of them do not understand more deeply the meaning and simbols of the motifs in tembe nggoli.